Can Self-Esteem Help Teens Resist Unhealthy Influence of Materialistic Goals Promoted By Role Models? - Zawadzka, Anna Maria; Borchet, Judyta; Iwanowska, Magdalena; Lewandowska-Walter, Aleksandra (Frontiers in Psychology, 2022)
The aim of the study was to examine the role of self-esteem in resisting the influence of materialistic goals of four social role models (mother, father, peers, and media) in adolescents (aged 13–16). Previous studies showed a negative correlation between the psychological health of teens and striving for materialistic goals, one of the main sources is the social modeling of materialism. Two studies were carried out. The first, correlational study, was conducted on target teens and their mothers, fathers, and peers of their choice. It examined if self-esteem is a moderator of the relationship between the materialism of social role models (mothers, fathers, peers, and media) and the materialism of teens. The second, experimental study, was conducted on target teens only. It examined how boosting the self-esteem of teens and activating materialism of social role models (mothers, fathers, peers, and media) may affect the materialism of teens. Study 1 showed a significant interaction effect of self-esteem and the materialism of peers on the materialism of teens. The interaction effects of self-esteem and other role models (parents and media) were not significant. Study 2 showed that elevated self-esteem lowered the influence of the materialism of peers on the materialism of teens. The results were not significant when other role models (parents and media) were analyzed. The results obtained in the presented studies indicate that the self-esteem of teens may have an important role in resisting the influence of materialism role models of peers. Practical implications of the studies for the psychological health of teens are also discussed.